Evaluating large-scale HIV prevention interventions: study design for an integrated mathematical modelling approach. Issue 7 (17th October 2007) - Boily, M-C; Lowndes, C M; Vickerman, P; Kumaranayake, L; Blanchard, J; Moses, S; Ramesh, B M; Pickles, M; Watts, C; Washington, R; Reza-Paul, S; Labbe, A C; et al.
Abstract : Background: There is an urgent need to evaluate HIV prevention interventions, thereby improving our understanding of what works, under what circumstances and what is cost effective. Objectives: To describe an integrated mathematical evaluation framework designed to assess the population-level impact of large-scale HIV interventions and applied in the context of Avahan, the Indian AIDS Initiative, in southern India. The Avahan Initiative is a large-scale HIV prevention intervention, funded by the Bill & Melinda Gates Foundation, which targets high-risk groups in selected districts of the six states most affected by the HIV/AIDS epidemic (Maharashtra, Karnataka, Tamil Nadu, Andhra Pradesh, Nagaland and Manipur) and along the national highways. Methods: One important component of the monitoring and evaluation of Avahan relies on an integrated mathematical framework that combines empirical biological and behavioural data from different subpopulations in the intervention areas, with the use of tailor-made transmission dynamics models embedded within a Bayesian framework. Results: An overview of the Avahan Initiative and the objectives of the monitoring and evaluation of the intervention is given. The rationale for choosing this evaluation design compared with other possible designs is presented, and the different components of the evaluation framework are described and its advantages and challenges are discussed, with illustrated examples. Conclusions: This is the first time such an approach has been applied on such a large scale. Lessons learnt from the CHARME project could help in the design of future evaluations of large-scale interventions in other settings, whereas the results of the evaluation will be of programmatic and public health relevance.